Gallbladder adenocarcinoma diagnosed retrospectively after initial resection of abdominal wall adenocarcinoma with unidentified primary source: a case report and review of the literature - Vignaroli, Kendall; Perez, Kevin; Guan, Angel; Kim, So Un; Raju, Sharmila; Leach, Carolyn; Ramiscal, Judi Anne B. (Frontiers in Oncology, 2025)
Gallbladder carcinoma is the most common malignancy found within the biliary tract and is most often diagnosed incidentally after cholecystectomy is performed. Port-site metastasis discovered after removal of gallbladder carcinoma is not entirely unusual; however, recommendations for the definitive management of these metastasis sites do not yet exist. We report a rare case of incisional site seeding diagnosed prior to the discovery of gallbladder adenocarcinoma in a healthy 59-year-old woman with a history of open cholecystectomy performed in a different country. Ultimately, this patient’s case was staged as stage IVb disease as determined by an extensive multidisciplinary tumor board discussion and was managed with observation, frequent physical exams, and surveillance imaging. Our patient’s survival is 2 years 7 months to date after index cholecystectomy. The management of our unprecedented case of gallbladder carcinoma diagnosed retrospectively after the initial discovery of incisional site metastasis is a difficult one, and the management of unique oncologic scenarios should utilize a multidisciplinary tumor board approach.